2021
DOI: 10.3390/cancers13071516
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of γ-H2AX and 53BP1 Foci in Peripheral Blood Lymphocytes to Predict Subclinical Hematotoxicity and Response in Somatostatin Receptor-Targeted Radionuclide Therapy for Advanced Gastroenteropancreatic Neuroendocrine Tumors

Abstract: Background: We aimed to characterize γ-H2AX and 53BP1 foci formation in patients receiving somatostatin receptor-targeted radioligand therapy, and explored its role for predicting treatment-related hematotoxicity, and treatment response. Methods: A prospective analysis of double-strand break (DSB) markers was performed in 21 patients with advanced gastroenteropancreatic neuroendocrine tumors. γ-H2AX and 53BP1 foci formation were evaluated in peripheral blood lymphocytes (PBLs) at baseline, +1 h and +24 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…This patient, however, showed no lymphocytopenia after one cycle of radioligand therapy. MIP maximum intensity projection, SUV standardized uptake value subject of future studies [20]. However, similar to our study, previous reports showed that the frequency of thrombocytopenia and leukocytopenia in patients under RLT is rather low [5,8,15,19].…”
Section: Discussionsupporting
confidence: 85%
“…This patient, however, showed no lymphocytopenia after one cycle of radioligand therapy. MIP maximum intensity projection, SUV standardized uptake value subject of future studies [20]. However, similar to our study, previous reports showed that the frequency of thrombocytopenia and leukocytopenia in patients under RLT is rather low [5,8,15,19].…”
Section: Discussionsupporting
confidence: 85%
“…As part of the study procedure, dedicated blood samples for the evaluation of DDR-markers were collected before administration of [ 177 Lu]Lu-PSMA-I&T, + 1 h after administration and + 24 h after administration. Blood samples were prepared as previously described in [22]. In brief, after isolating PBLs through Ficoll (GE Healthcare, Chicago, IL, USA) density-gradient from EDTA blood, PBLs from mCRPC patients were frozen in an RPMI1640 medium with 15% fetal calf serum 500 U/ml penicillin, 0.5 mg/ml streptomycin, and 2 mM l-glutamine, supplemented with 10% glycerol at − 80 °C until further use.…”
Section: Assessment Of Ddr-markersmentioning
confidence: 99%
“…Finally, DAPI (Invitrogen) was used to counterstain DNA and cells were mounted with ProLong® Gold (Invitrogen). Further details can be found in [22].…”
Section: Assessment Of Ddr-markersmentioning
confidence: 99%
See 2 more Smart Citations